Beyond Bergmann's rule: size–latitude relationships in marine Bivalvia world‐wide. Issue 2 (14th June 2012) - Berke, Sarah K.; Jablonski, David; Krug, Andrew Z.; Roy, Kaustuv; Tomasovych, Adam
ABSTRACT: Aim  Variations in body size are well established for many taxa of endotherms and ectotherms, but remain poorly documented for marine invertebrates. Here we explore how body size varies with latitude, temperature and productivity for a major marine invertebrate class, the Bivalvia. Location  Continental shelves world‐wide. Methods  We used regression models to assess univariate relationships between size and latitude as well as multivariate relationships between size, latitude and environmental parameters (mean and seasonality in temperature and mean productivity). The dataset consisted of 4845 species in 59 families from shelf depths at all latitudes in the Pacific and Atlantic oceans. We also used Blomberg's K to assess whether size–latitude relationships show phylogenetic signal, and test whether functional groups based on feeding mode, substrate relationships, mobility and fixation can account for observed size–latitude trends. Results  Size–latitude trends are taxonomically and geographically common in bivalves, but vary widely in sign and strength – no simple explanations based on environmental parameters, phylogeny or functional group hold across all families. Perhaps most importantly, we found that the observed trends vary considerably between hemispheres and among coastlines. Main conclusions  Broadly generalizable macroecological patterns in inter‐specific body size may not exist for marine invertebrates. Although size–latitude trends occur in many bivalve lineages, the underlying mechanisms evidently differ among regions and/or lineages. Fully understanding macroecological patterns requires truly global datasets as well as information about the evolutionary history of specific lineages and regions.